Sustainability Outlook of Thermochemical-Based Second-Generation Biofuel Production: Exergy Assessment - Samir Meramo; Plinio Puello; Julio Rodríguez (Applied Sciences, 2021)
Since the last century, the idea of replacing traditional fossil sources with renewable alternatives has attracted much attention. As a result, auspicious renewable biofuels, such as biohydrogen or bio-oil, have emerged as suitable options. This study provides some knowledge on combining process design, modeling, and exergy analysis as a united framework to support decision making in energy-based projects. The assessment also included a final evaluation, considering sustainability indicators to evaluate process performance. Feedstock selection is crucial for producing bio-oil and hydrogen for process sustainability; this aspect is discussed, considering second-generation sources. Second-generation bio-oil and biohydrogen production are assessed and compared under the proposed framework. Process simulation was performed using ASPEN PLUS. Exergy analysis was developed using data generated in the process simulation stage, containing material and energy balances, thermodynamic properties, chemical reactions, etc. A mathematical formulation for the exergy analysis shows the exergy of utilities, waste, exergy efficiency, and exergy intensity of both processes, based on the same functional unit (1 kg of product). The sustainability evaluation included quantifying side parameters, such as the renewability index, energy efficiency, or global warming potential. The results indicate that pyrolysis obtained the highest resource exergy efficiency (11%), compared to gasification (3%). The exergy intensity shows that more exergy is consumed in the gasification process (4080.21 MJ/kg) than pyrolysis (18.64 MJ/kg). Similar results are obtained for total irreversibility (327.41 vs. 48.75 MJ/kg) and exergy of wastes (51.34 vs. 18.14 MJ/kg).